Iopamidol degradation with ZVI- and ZVA-activated chemical oxidation: Investigation of toxicity, anaerobic inhibition and microbial communities. Issue 6 (December 2018) - Yangin-Gomec, Cigdem; Olmez-Hanci, Tugba; Arslan-Alaton, Idil; Khoei, Shiva; Fakhri, Hadi
Graphical abstract: Highlights: Iopamidol removal was achieved with activated hydrogen peroxide and persulfate. Different iopamidol toxicities towards V. fischeri and P. subcapitata were evident. No inhibition was apparent in the biogas yield during anaerobic digestion. Slight changes in microbial communities populated by Firmicutes as bacterial phylum. Methanospirillum was the dominant archaeal genus. Abstract: Treatment of aqueous iopamidol (IOPA, 2 mg/L), an iodinated organic X-ray contrast chemical and micropollutant, with nano-sized zero-valent iron (ZVI) and aluminum (ZVA)-activated hydrogen peroxide (HP) and persulfate (PS) oxidation processes was investigated. Changes in acute toxicity, anaerobic digestion, biogas yield and microbial community were further examined to question the ecotoxicological safety and bioamenability of the proposed treatment systems. For this purpose, two different bioassays were conducted with V. fischeri and P. subcapitata . The cumulative biogas production was monitored in batch anaerobic digestion tests. The microbial community was identified by Illumina MiSeq next generation sequencing (NGS) technology and abundant bacteria and archaea were analysed in the biomass samples taken from anaerobic reactors. The application of activated HP (1.00 mM) and PS (0.50 mM) treatments under acidic conditions (pH 3) resulted in complete IOPA removal. The original IOPA sample caused 5% and 74% inhibitions to V. fischeri and P. subcapitata, respectively. The relative inhibition towards P. subcapitata increased from 74% to 97% and 93% after 5 min HP/ZVI and 120 min PS/ZVA treatments, respectively. No meaningful changes in terms of digestion performance and cumulative biogas production in the presence of untreated and HP/ZVI- or PS/ZVA-treated IOPA samples were evidenced. Moreover, all biomass samples were populated by a bacterial consortium related to different members of Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria . Hydrogenotrophic ( Methanospirillum, Methanobacterium) and acetoclastic ( Methanosaeta, Methanosarcina) methanogens were the prevalent members of archaea at genus level. An increase in relative abundance was only identified in Methanobacterium under the phylum namely Euryarchaeota .